Development of Multimedia-Based Sex Education Media in Efforts to Educate Parents in Betung Village, Abab District - Alwi, Tomas; Nengsih, Yanti Karmila; Shomedran, Shomedran (Universitas Negeri Padang, 2024)
This study aims to develop multimedia-based sex education media as a valid and practical parental education effort using the Research and development (RnD) research method, with the Borg and Gall development model implemented in Betung Village, Abab District. There were 21 subjects in the study, with the following stages: initial data collection, product design, product validation, product revision, and product testing. The data collection technique used in this study was a questionnaire which produced a product in the form of animas Sex Education video media. The implementation of animated video media was carried out in two stages, namely one-to-one trials and small group trials. The results of this study are sex education media in the form of animated videos which have a validity level on the language aspect getting a total score of 28 with a percentage of 77%, material aspects getting a total score of 34 with a percentage of 94%, and the media aspect getting a total score of 35 with a percentage of 97%. . Based on the validation results, it can be concluded that the development of sex education media in an effort to educate parents is categorized as very valid or very practical